Correction: Neural Correlates of Musical Creativity: Differences between High and Low Creative Subjects (PloS one, 2014)
The legend for Figure 2, “Example of a creation during the Creative Task,” appears as a paragraph below the figure in the HTML version of the paper and as the first paragraph in the left column on page 5 of the PDF version of the paper. The letters (a), (b), and (c) denote arbitrary rhythm cell segmentations used for punctuation. https://doi.org/10.1371/journal.pone.0075427.g002 1.